"Visit truly Asia Malaysia": Analysing VMY 2020 tourism promotional video - Abdul Razak, Norhanim (Academia Industry Networks, 2020)
Tourism Malaysia has adopted the tagline “Malaysia Truly Asia” in projecting this country to tourists since 1999. Branding Malaysia as an Asian destination has been a wellestablished theme in marketing Malaysian tourism. As a result of this, Ministry of Tourism, Arts and Culture has retained Asia as a unique tourism brand and identity in the launching of Visit Malaysia 2020 campaign. However, the slogan has been slightly rephrased to “Visit Truly Asia Malaysia”. Because of the importance of Asia as a Malaysian tourism brand for two decades, this paper aims to explore how the national tourism authority of Malaysia portrayed the recent tourism campaign “Visit Truly Asia Malaysia” in the official promotional video. Utilising a discourse analysis method, visuals and the textual content through lyrics of the song were assessed to uncover how this country has been framed as part of the theme “Visit Truly Asia Malaysia”. The assessment of the promotional video uncovered that the projection of “Truly Asia” primarily reflects multi-ethnicity of Malaysian societies and unity in diversity as core attractions in the official video. This is manifested through the portrayal of their colourful cultural heritage attributes, particularly traditional costumes, traditional music and performing arts, musical instruments, and gastronomy. Diverse spectacular natural resources, such as tropical rainforests, wildlife, beaches and highlands, are also parts of “Truly Asia” projection. The overall assessment of the promotional video identified that the portrayal of Malaysia as a tourist destination adopted some attributes of Orientalism, particularly fascinating traditional cultural heritage attributes and natural resources in order to highlight Otherness uniqueness and exoticness. Aspects of modernity and familiarity are depicted through cosmopolitan cities and Western lifestyles.